1999
DOI: 10.1159/000028051
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Substance P Receptors in Normal and Psoriatic Skin

Abstract: Recently, sustance P receptors (SPR) have been detected in neonatal foreskin. Our purpose was to determine the expression of SPR in other localizations than neonatal foreskin. As SP has been implicated in the pathogenesis of inflammatory cutaneous lesions, we wondered whether SPR localization was modified in psoriatic lesions. In normal skin, SP binding sites were detected using biotinylated SP and abrogated by a specific NK1 antagonist (spantide) on blood vessels, sweat glands and hair follicles. In the norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 22 publications
(26 reference statements)
0
21
0
1
Order By: Relevance
“…Use of biotinylated SP suggested that NK-1 expression may be increased in keratinocytes from psoriatic plaques (71). Another study showed mast cells express the NK-1 receptor in both affected and unaffected psoriatic skin (6).…”
Section: Discussionmentioning
confidence: 99%
“…Use of biotinylated SP suggested that NK-1 expression may be increased in keratinocytes from psoriatic plaques (71). Another study showed mast cells express the NK-1 receptor in both affected and unaffected psoriatic skin (6).…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocytes express receptors for SP (neurokinin 1) and CGRP (CRLR, RAMP1 and RAMP2)(10,3032), and previous reports have provided data demonstrating that epidermal and other types of epithelial cells produce IL-1β in response to neuropeptide stimulation (33). Moreover, we had previously demonstrated that in vivo direct application of SP to mouse hindpaw skin results in an increased production of IL-1β (3).…”
Section: Discussionmentioning
confidence: 99%
“…In the skin, there are several NK 1 receptor-expressing cells, including keratinocytes, 18,20,21) Langerhans cells, 22) endothelial cells, 23) macrophages, 24) the sensory nerve terminal, 25) and mast cell. 26) It is worth to examine which cells would be affected by repeated administration of Unseiin.…”
Section: Discussionmentioning
confidence: 99%